Effect of low and medium environmental temperatures on physiological and reproductive parameters in Soay rams - Pointing, Stephen William (The University of Edinburgh, 1981)
Seven adult Soay rams, which had been cranially sympathectomised, were used to study the effect of a low (7°C) and medium (15°C) environmental temperature on three physiological parameters (body temperature, heart rate and respiration rate) and two reproductive parameters (testis diameter and plasma testosterone concentration). They were kept in a controlled temperature room with artificial lighting conditions of eight hours light and 16 hours dark (8L:16D). There was a short adaptation period, followed by three weeks at 7°C and three weeks at 1^°C. Adequate food and water was present at all times. Results showed that body temperature was lower during the 7°C period than the 15°C period (P < 0.05). All the other results were not significant but certain trends were noticed. The heart rate was greater during the cool period compared with the warmer period; and the respiration rate was higher during the warm period. The testis diameter increased from the beginning of the 7°C period to reach a maximum size at the end of the initial period; at the higher temperature (15°C) testis diameter gradually decreased. Testosterone concentrations were high throughout the whole experimental period but the levels were greater during the 15°C period compared with the 7°0 period. It was concluded that although light acts as the major stimulus to the onset of the breeding season in rams, low temperature alone plays a significant role, and the maximum effect is due to a combination of the two factors.
The effect of low and medium environmental temperatures on physiological and reproductive parameters in Soay rams
Keywords: Annexe MSc Digitisation Project 2022 Block 46; Soay rams; cranially sympathectomised; 7°C environmental temperature; 15°C environmental temperature; physiological parameters; reproductive parameters; controlled temperature; artificial lighting